Efforts to Improve the Ability to Read Aloud Using Picture Story Media in Indonesian Language Subjects at SD Negeri 095 North Bengkulu - Alifya Yunitasari; Miyarsih Kusumastuti; Nora Alisa Pulungan (Education Achievement: Journal of Science and Research, 2024)
Indonesian students' reading skills at SD Negeri 095 North Bengkulu Province will be improved through the use of picture story media. Located in Bengkulu. Classroom action research which includes two cycles is the core of this research. Ten second grade students at SD Negeri 095 North Bengkulu Province, Bengkulu, took part in the research in the 2023–2024 school year. This research data comes from a combination of tests, observations and documentation. We used descriptive statistics to average the quantitative data and data from observation notes to assess the qualitative data. Based on the research results, a reading aloud method using picture story media has been developed for class II students at SD Negeri 095, North Bengkulu Province. Bengkulu academic year 2023–2024. Students' ability to read aloud increases due to exposure to interesting visual story media. Student learning outcomes in the pre-cycle show this; Their average was 64.1, but by the end of the first cycle, they had improved to 66.6. Meanwhile, the average score in cycle II was 78.3, an increase from cycle I. Completed 20%, 40% and 80% of the pre-cycle, cycle I and cycle II respectively.